Effect of ambulatory versus hospital treatment for gestational diabetes or hyperglycemia on infant mortality rates: a systematic review - Rudge, Marilza Vieira Cunha [UNESP]; Lima, Silvana Andréa Molina [UNESP]; Dib, Regina Paolucci El [UNESP]; Marini, Gabriela; Magalhaes, Claudia; Calderon, Iracema de Mattos Paranhos [UNESP] (Associação Paulista de Medicina (APM), 2013)
CONTEXTO E OBJETIVO:Gestações complicadas pelo diabetes estão associadas com aumento das complicações neonatais e maternas. A complicação mais grave materna é o risco de desenvolver diabetes tipo 2 após 10-12 anos do parto. Para o controle rigoroso da glicose no sangue, as mulheres grávidas são tratadas de forma ambulatorial ou com internações hospitalares. O objetivo deste estudo é avaliar a efetividade do tratamento ambulatorial versus hospitalização em gestações complicadas por diabetes ou hiperglicemia.TIPO DE ESTUDO E LOCAL:Revisão sistemática conduzida em hospital universitário público.MÉTODOS:Uma revisão sistemática da literatura foi realizada e as principais bases de dados eletrônicas foram pesquisadas. A data da pesquisa mais recente foi 4 de setembro de 2011. Dois autores selecionaram independentemente os ensaios clínicos relevantes, avaliaram a qualidade metodológica e extraíram os dados.RESULTADOS:Apenas três estudos foram selecionados, com tamanho de amostra pequeno. Não houve diferença estatisticamente significativa entre o tratamento ambulatorial versus hospitalização em relação à mortalidade em nenhuma das subcategorias analisadas: mortes perinatais e neonatais, (risco relativo [RR] 0,65; 95% de intervalo de confiança [IC] 0,11-3,84, P = 0,63); morte neonatal (RR 0,29, IC 95% 0,01-6,07, P = 0,43), e óbitos infantis (RR 0,29, IC 95% 0,01-6,07, P = 0,43).CONCLUSÕES:Com base em estudos com risco de viés alto ou moderado, esta revisão demonstrou que não há diferença estatisticamente significante entre o tratamento ambulatorial comparado com o hospitalar na redução das taxas de mortalidade em gestações complicadas por diabetes ou hiperglicemia. Esta revisão sistemática também sugere a necessidade de mais ensaios clínicos randomizados sobre o assunto.

CONTEXT AND OBJECTIVE:Pregnancies complicated by diabetes are associated with increased neonatal and maternal complications. The most serious maternal complication is the risk of developing type 2 diabetes, 10-12 years after the delivery. For rigorous control over blood glucose, pregnant women are treated through ambulatory management or hospitalization. The aim of this study was to evaluate the effectiveness of ambulatory management versus hospitalization in pregnancies complicated by diabetes or hyperglycemia.DESIGN AND SETTING:Systematic review conducted in a public university hospital.METHODS:A systematic review of the literature was performed and the main electronic databases were searched. The date of the most recent search was September 4, 2011. Two authors independently selected relevant clinical trials, assessed their methodological quality and extracted data.RESULTS:Only three studies were selected, with small sample sizes. There was no statistically significance different between ambulatory management and hospitalization, regarding mortality in any of the subcategories analyzed: perinatal and neonatal deaths (relative risk [RR] 0.65; 95% confidential interval [CI]: 0.11 to 3.84; P = 0.63); neonatal deaths (RR 0.29; 95% CI: 0.01 to 6.07; P = 0.43); and infant deaths (RR 0.29; 95% CI: 0.01 to 6.07; P = 0.43).CONCLUSIONS:This review, based on studies with high or moderate risk of bias, showed that there was no statistically significant difference between ambulatory management and hospital care, regarding reduction of mortality rates in pregnancies complicated by diabetes or hyperglycemia. It also suggested that there is a need for further randomized controlled trials on this issue.
Efeito do tratamento ambulatorial versus hospitalar de diabetes ou hiperglicemia gestacional nas taxas de mortalidade infantil: revisão sistemática
Keywords: Diabetes gestacional; Assistencia ambulatorial; Hospitalizacao; Revisao; Ensaios clinicos como assunto; Diabetes, gestational; Ambulatory care; Hospitalization; Review [publication type]; Clinical trials as topic